SYSTEMATIC LITERATURE REVIEW: PROFIL PROSES BERPIKIR SISWA SMP BERDASARKAN TAHAPAN PEMECAHAN MASALAH MATEMATIS - Afni Rifani; Heni Pujiastuti; Nurul Anriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Thinking process is a crucial aspect in mathematical problem solving that has rarely been examined comprehensively through a synthesis approach. The purpose of this investigation is to examine the profile of junior high school student’s thinking processes based on Polya’s mathematical problem-solving stages and identify the factors that influence them. A systematic literature review (SLR) in accordance with PRISMA 2020 standards is the methodology employed. Three databases, Google Scholar, Garuda, and SINTA were searched for articles from 2020 to 2026. Based on a selection process using predetermined inclusion and exclusion criteria, 14 articles were deemed eligible for synthesis. The synthesis results indicate that the thinking process profiles of junior high school students vary across each stage of Polya’s model. These variations in thinking processes were influenced by student’s internal factors, including prior mathematical ability, adversity quotient, gender, and emotional intelligence. These findings imply the need for mathematics learning that is designed with attention to the quality od student’s thinking processes at each stage rather than focusing solely on final answers. Problem-based learning and scaffolding are suggested as relevant strategies to support the comprehensive development of junior high school student’s mathematical problem-solving abilities.